(untitled) (Research, Society and Development, 2022)
Faced with the COVID-19 pandemic, caused by the SARS-Cov-2 virus, numerous psychosocial problems were triggered and/or worsened, which can have a direct influence on patients’ oral health, promoting or intensifying orofacial changes and in the stomatognathic system, such as bruxism and, consequently, temporomandibular disorders (TMDs). The objective of this work was to carry out a literature review about the influence of anxiety, caused by the COVID-19 pandemic, on the symptoms associated with bruxism and temporomandibular disorders. This is a narrative literature review, with a documentary and observational approach. The databases for the literature search were PubMED, SCIELO, LILACS and Google Scholar. The keywords used were “local anesthetics”, “dental care”, “pregnant women”, “dental care for children”, “dental care for the chronically ill” and “dental care for the elderly”. The COVID-19 pandemic led to the emergence of several problems with direct and indirect interference in oral health, and these changes may be related to contamination by the SARS-CoV-2 virus or from the stress and anxiety caused by the pandemic itself. Therefore, the literature shows that the psychosocial factors linked to the COVID-19 pandemic significantly increased the frequency, intensity and duration of parafunctional habits, contributing to the emergence of episodes of bruxism and TMD. The advent of the pandemic caused by the new coronavirus may be associated with increased levels of stress, anxiety and depression. These changes are correlated with worsening symptoms of temporomandibular disorders and bruxism.